Nature or Nurture in Higher Education? Inter-generational Implications of the Vietnam-Era Lottery - Louis N. Christofides; Michael Hoy; Joniada Milla; Thanasis Stengos (Institute for the Study of Labor (IZA), 2015)
It is evident that a strong positive correlation persists between the educational attainment of parents and that of their children in many, if not most, populations. This relationship may form an important part of the phenomenon of low social mobility as well as inefficiently low investment in human capital by youth who have parents with relatively low educational attainment. Is it a genetic inter-generational transmission of innate ability from parents to their children (i.e. nature) or is it the environment that the better educated parents provide for their children (i.e. nurture) that explains this positive relationship? Understanding the relative contributions of nature versus nurture is critical to the development of any social policy designed to increase social and economic mobility between generations. Separating the so-called nature and nurture effects of this relationship is a difficult task. We use the Vietnam Era Draft Lottery as a natural experiment to address the nature-nurture question. Attending university in order to avoid the draft created a cohort which included individuals who would not normally have attended post-secondary educational institutions. Comparing the educational attainment of children of this cohort to that of cohorts who attended university in "normal times" creates a natural experiment to test the relative importance of the nature or nurture explanations. Our findings provide evidence in support of the nurture argument.
Keywords: I0; 330; inter-generational mobility; higher education attendance